2012
DOI: 10.1111/j.1728-4465.2012.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Sexual Empowerment and Contraceptive Use in Ghana

Abstract: Pervasive gendered inequities and norms regarding the subordination of women give Ghanaian men disproportionately more power than women, particularly in relation to sex. We hypothesize that lack of sexual empowerment may pose an important barrier to reproductive health and adoption of family planning methods. Using the 2008 Ghana Demographic Health Survey, we examine the association between women's sexual empowerment and contraceptive use in Ghana among nonpregnant married and partnered women not desiring to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 48 publications
16
71
0
Order By: Relevance
“…Right to contraceptives use is a component of reproductive health rights and cannot be ignored. Our study findings are in consonance with results of a study in Ghana where women's increasing levels of sexual empowerment were found to be associated with increased use of contraceptives (Crissman et al, 2012). The sexual rights are directly linked to contraceptive uptake and this could explain this strong association.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Right to contraceptives use is a component of reproductive health rights and cannot be ignored. Our study findings are in consonance with results of a study in Ghana where women's increasing levels of sexual empowerment were found to be associated with increased use of contraceptives (Crissman et al, 2012). The sexual rights are directly linked to contraceptive uptake and this could explain this strong association.…”
Section: Discussionsupporting
confidence: 81%
“…Among businesswomen in Kampala, a study established higher figures of contraceptive uptake than both the national average and the urban estimates at the time (Kwagala, 1996) and economic empowerment was associated with use of modern contraceptives (Kibira, 2009), while Crissman in Ghana found women's increasing levels of sexual empowerment to be associated with increased use of contraceptives (Crissman et al, 2012).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Based on these results, we speculate that economic empowerment of households in Zambia will reduce the economic expectations of parents from children. Wealth has previously been reported as a contributor to contraceptive use among women in developing countries, with wealthier women having more access to and utilisation of birth control measures [24,25]. Crissman [24] found that increasing wealth was one of the main factors associated with contraceptive use among non-pregnant married and partnered women who did not want to get pregnant in the next three months in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…However, preceding research shows that the mediation of empowerment significantly increases contraception practice rate [26], and that women with higher levels of empowerment have higher rates of contraception practices and birth control practices [29]. As such, sex-related empowerment is an important predictive factor for intentions and practice of contraception.…”
Section: Discussionmentioning
confidence: 99%